PRINSIP DASAR PENDIDIKAN ANAK MENURUT PERSPEKTIF AL-QUR’AN - ., Rosdiana (Idaarah: Jurnal Manajemen Pendidikan, 2017)
The aims of children education in Al-Qur’an is a process of guiding from the tutor (parents or teachers) persistenty towards the physical, spritial, ad intelligence’s children development to the formation of the good moslems. There are ten basic principles of children education need to be understood by all of the tutors in teaching based on Al-Qur’an perspective, namely: accepting the children in the way they are, as a child is a trust, educate the children according to capability, reminds that the main purpose of educating the children is in order to be liberated them from the Fire. The parents are required to strive but Allah SWT remains control the result. The parents are also required to be a good model for the children, to give the best advice, to educate not only their physical but also their spiritual, to educate the children according to their natural tendencies and do not stop it until apart. Allah SWT creates human and give a proper guidance in Al-Qur’an about the way to educate. If every tutors take Al-Qur’an as their guidance in educating the children, then they will bear the best intelligent generation with a good behavior and having a good social capacity based on the sincerely dedication to Allah SWT.